Tissue proteomics of splenic marginal zone lymphoma. Issue 14 (20th May 2015) - Polati, Rita; Brandi, Jessica; Dalai, Irene; Zamò, Alberto; Cecconi, Daniela
<x xml:space="preserve">Abstract</x> Splenic marginal zone lymphoma (SMZL) is a rare chronic B lymphoproliferative disease, whose molecular pathogenesis has still not been well established. For the first time, a proteomic approach was undertaken to analyse the protein profiles of SMZL tissue. 1D and 2D Western blot, immunohistochemical analysis, and functional data mining were also performed in order to validate results, investigate protein species specific regulation, classify proteins, and explore their potential relationships. We demonstrated that SMZL is characterized by modulation of protein species related to energetic metabolism and apoptosis pathways. We also reported specific protein species (such as biliverdin reductase A, manganese superoxide dismutase, beta‐2 microglobulin, growth factor receptor‐bound protein 2, acidic leucine‐rich nuclear phosphoprotein 32 family member A, and Set nuclear oncogene) directly involved in NF‐kB and BCR pathways, as well as in chromatin remodelling and cytoskeleton. Our findings shed new light on SMZL pathogenesis and provide a basis for the future development of novel biomarkers. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium with the dataset identifier PXD001124.